The Influence of Kerosene to Increase the Quality of Coal from Bayah South Banten Using UBC Methode - Heriyanto, Heri; Ernayati, Widya; Yulvianti, Meri; Sutijan, Sutijan (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2015)
The increasing price and the decreasing stock of fossil fuel nowadays are two factorsthat make the use of alternative fuel with lower price become necessity. The source ofenergy that can be used to fill the gap between convensional fossil fuel towards cleanerand renewable energy is Coal. South Banten has a massive stock of coal, around 70% ofall the mineral sources in South Banten, but the quality of the coal is low, due to thesulfur content around 2.28 % dry basis and a high water content that lead to the lowestcalor content. The aim of this research is to lowering the sulfur and water content ofthe coal. Upgrading Brown Coal methode is the methode used to reach the aim stated.The research was settle at temperature 150: C, pressure 350 kPa, and addition ofkerosene as the solvent. The result of the research shows the increasing of calorcontent and the decreasing sulfur content when the evaporation temperature graduallyincreased.